2015
DOI: 10.1038/tp.2015.120
|View full text |Cite
|
Sign up to set email alerts
|

Elevated baseline serum glutamate as a pharmacometabolomic biomarker for acamprosate treatment outcome in alcohol-dependent subjects

Abstract: Acamprosate has been widely used since the Food and Drug Administration approved the medication for treatment of alcohol use disorders (AUDs) in 2004. Although the detailed molecular mechanism of acamprosate remains unclear, it has been largely known that acamprosate inhibits glutamate action in the brain. However, AUD is a complex and heterogeneous disorder. Thus, biomarkers are required to prescribe this medication to patients who will have the highest likelihood of responding positively. To identify pharmac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 50 publications
5
41
0
Order By: Relevance
“…Lower craving scores have been reported by our previous study to be associated with acamprosate treatment response 28 . Furthermore, our group has also found that increased alcohol craving is associated with shorter abstinence 18 .…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Lower craving scores have been reported by our previous study to be associated with acamprosate treatment response 28 . Furthermore, our group has also found that increased alcohol craving is associated with shorter abstinence 18 .…”
Section: Discussionsupporting
confidence: 66%
“…We utilized metabolomics data from a subset of 120 subjects recruited as part of a previously described study 18, 28 . All participants met DSM-IV-TR criteria for alcohol dependence.…”
Section: Methodsmentioning
confidence: 99%
“…This pattern has been confirmed in a recent meta‐analysis investigating the time frame in which acamprosate was found to be of therapeutic value (Maisel et al ., ). As proposed by Nam et al ., serum glutamate could be used as a biomarker for the efficacy of acamprosate in order to personalize anti‐dependence therapy (Nam et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Thus, should a medication become available that blocks CRF or facilitates NPY neurotransmission, one could speculate that some specific human genetic subgroups might be more responsive. Indeed, observations in a clinical study of AUD treatment with acamprosate that baseline serum glutamate levels are significantly higher in responders compared with non-responders and that serum glutamate levels of responders are normalized after acamprosate treatment, whereas there was no significant glutamate change in non-responders, suggest that there is a genetic predisposition that can predict responsiveness to acamprosate, suggesting ultimately a means of predicting which patients are likely to respond to which medication (Nam et al, 2015). …”
Section: Neurobiological Mechanisms In Alcohol Use Disorder That Are mentioning
confidence: 99%